2021
DOI: 10.1049/syb2.12038
|View full text |Cite
|
Sign up to set email alerts
|

RYR2mutation in non‐small cell lung cancer prolongs survival via down‐regulation ofDKK1and up‐regulation ofGS1‐115G20.1: A weighted gene Co‐expression network analysis and risk prognostic models

Abstract: RYR2 mutation is clinically frequent in non‐small cell lung cancer (NSCLC) with its function being elusive. We downloaded lung squamous cell carcinoma and lung adenocarcinoma samples from the TCGA database, split the samples into RYR2 mutant group (n = 337) and RYR2 wild group (n = 634), and established Kaplan‐Meier curves. The results showed that RYR2 mutant group lived longer than the wild group (p = 0.027). Weighted gene co‐expression network analysis (WGCNA) of differentially expressed genes (DEGs) yielded… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 56 publications
(64 reference statements)
0
5
0
Order By: Relevance
“…TP53 status was a reliable and robust immune signature for identifying early-stage LUAD patients with a high risk of unfavorable survival [ 49 ]. TCGA data demonstrated that the RYR2 mutant group lived longer than the wild group [ 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…TP53 status was a reliable and robust immune signature for identifying early-stage LUAD patients with a high risk of unfavorable survival [ 49 ]. TCGA data demonstrated that the RYR2 mutant group lived longer than the wild group [ 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…Wang et al found that Rac3 acted on TFDP1, CCND1 , and MYC to regulate cell proliferation of LUAD during tumorigenesis [ 50 ]. Ren et al found that RYR2 mutation could lead to a better prognosis by downregulation of DKK1 , which was associated with TP53 , MTOR , and VEGF in NSCLC [ 51 ]. Therefore, the specific mechanism of genes cooccurred with TFDP1 alterations in LUAD may be worth further research.…”
Section: Discussionmentioning
confidence: 99%
“…Liu et al found the RYR2 mutation was linked to a greater TMB and a better clinical outcome by enhancing the antitumor immune response in breast cancer and esophageal adenocarcinoma [ 26 ]. In nonsmall cell lung cancer, RYR2 mutation may prolong survival via downregulation of DKK1 and upregulation [ 27 ]. In this study, we found that RYR2 expression was negatively related to the PFS in CRC.…”
Section: Discussionmentioning
confidence: 99%